2014
DOI: 10.1021/ja502851h
|View full text |Cite
|
Sign up to set email alerts
|

A Genetically Encoded aza-Michael Acceptor for Covalent Cross-Linking of Protein–Receptor Complexes

Abstract: Selective covalent bond formation at a protein–protein interface potentially can be achieved by genetically introducing into a protein an appropriately “tuned” electrophilic unnatural amino acid that reacts with a native nucleophilic residue in its cognate receptor upon complex formation. We have evolved orthogonal aminoacyl-tRNA synthetase/tRNACUA pairs that genetically encode three aza-Michael acceptor amino acids, Nε-acryloyl-(S)-lysine (AcrK, 1), p-acrylamido-(S)-phenylalanine (AcrF, 2), and p-vinylsulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 45 publications
(90 reference statements)
1
89
0
3
Order By: Relevance
“…These longer and more flexible linkages should make it much easier to cross-link sites within proteins. Indeed, it has recently been shown that electrophilic amino acids with extended structures can selectively stabilize proteins and protein complexes by intra-and intermolecular cross-links, respectively (13,(23)(24)(25). However, the use of electrophilic NCAAs to form noncanonical cross-links in a bacterial selection system can be complicated by cellular toxicity, irreversible reactions, reaction rates, and scavenging by intracellular nucleophiles.…”
Section: Discussionmentioning
confidence: 99%
“…These longer and more flexible linkages should make it much easier to cross-link sites within proteins. Indeed, it has recently been shown that electrophilic amino acids with extended structures can selectively stabilize proteins and protein complexes by intra-and intermolecular cross-links, respectively (13,(23)(24)(25). However, the use of electrophilic NCAAs to form noncanonical cross-links in a bacterial selection system can be complicated by cellular toxicity, irreversible reactions, reaction rates, and scavenging by intracellular nucleophiles.…”
Section: Discussionmentioning
confidence: 99%
“…Proximity-enabled reactivity of ''tuned'' electrophilic NNAAs towards nucleophilic natural amino acids can also be used to probe protein-protein interaction. Selective formation of irreversible covalent bond between a specific lysine of a cancer biomarker ErbB2 and VSF genetically incorporated into anti-ErbB2 Fab was confirmed in vitro and in vivo (Furman et al, 2014). This type of NNAAs has a promise for identifying unknown interacting partners of a target protein, especially those with a large dissociation constant.…”
Section: Biochemical Analysismentioning
confidence: 78%
“…As a result of UV irradiation, a covalently-linked GST dimer was formed when BZF was placed in the dimer interface, but no crosslinking occurred when placed outside the interface. Functional groups targeting specific natural amino acids in a spontaneous and proximity-enhanced manner have been genetically encoded through evolved pairs of amber suppressor tRNA/aaRS (VSF, BCK and ACK; Figure 2) Furman et al, 2014;Xiang et al, 2013;Xiang et al, 2014). These NNAAs have electrophilic residues that selectively react with proximal nucleophiles such as lysine, histidine and cysteine ( Figure 1).…”
Section: Proximity-enabled Bond Formation With a Natural Amino Acidmentioning
confidence: 99%
“…Unless otherwise mentioned, all other chemicals were purchased from Sigma-Aldrich and used without further purification. AcrF was synthesized as described (47). Absorbance spectra were measured with a Hewlett-Packard 8453 UV-visible spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%